Potential value of pre- and post-therapy [68Ga]Ga-DOTA-TATE PET/CT in the prognosis of response to PRRT in disseminated neuroendocrine tumors - Opalińska, Marta; Morawiec-Sławek, Karolina; Kania-Kuc, Adrian; Al Maraih, Ibraheem; Sowa-Staszczak, Anna; Hubalewska-Dydejczyk, Alicja (Frontiers in Endocrinology, 2022)
Background Peptide receptor radionuclide therapy (PRRT) is one of the most effective therapeutic options for metastatic, well-differentiated neuroendocrine tumors (NETs). It improves progressive disease-free survival and enables to control of hormone secretion in the functioning tumors. Currently, there are no clearly established predictors of responses to PRRT. The main factors hindering such prediction are the heterogeneity of somatostatin receptors expression within and between lesions, lack of standardized parameters for functional imaging and the use of different PRRT protocols. The main goal of our study was to quantify SUVmax changes, which reflect the expression of somatostatin receptors in tumor tissues, in the [68Ga]Ga-DOTA-TATE PET/CT scans, as a potential predictors of a long-term response to PRRT. Material and methods Out of 20 patients treated with PRRT using [177Lu]Lu and/or [177Lu]Lu /[90Y]Y-DOTA-TATE in 2017-2019 due to dissemination of NET, 12 patients underwent [68Ga]Ga-DOTA-TATE PET/CT on average 3.1months before and 4.5 months after PRRT and were eligible for the analysis. In total 76 metastatic lesions were evaluated. SUVmax were measured for every lesion in both PET/CTs(before and after PRRT). Those values were corrected by liver SUVmax and liver SUV mean measured in volumetric analysis and specified as SUVlmax and SUVlmean. As a next step SUVlmax and SUVlmean change was counted on the basis of both PET/CTs were correlated with the clinical outcome assessed as progressive disease (PR), disease stabilization (SD) or partial response (PR). Results The mean follow-up was 19.9 months, PD, SD and PR was found in 5, 5 and 2 patients, respectively. Among PR patients, the decrease in mean SUVlmax compared with baseline was 66.3%. The corrected SUVlmax change by 30.3% in the patients with SD. The values of corrected SUVlmax change increased on mean by 9.1% in patients with PD. The SUVlmean changes were -69,8%, -30.8% and -3.7% respectively. Conclusions A decrease of the SUVmax value in metastatic lesions corrected by the normal liver tissue uptake assessed in [68Ga]Ga-DOTA-TATE PET/CT indicate a lower risk of NET progressive disease within 20 months after completion of PRRT and may constitute an additional, independent parameter for estimation of the overall risk of disease progression.